Saneamento básico: estudo do caso de Arroio Grande,RS - Godecke, Marcos Vinicius; Decker, Anderson Tiago (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
On the numerous environmental problems include those related to sanitation, important for reflecting directly on the quality of life of the populations. As a way to reverse the current framework, the federal legislation, in particular the law 11,445/2007, demand the establishment of a Municipal Plan of Basic Sanitation (PMSB). This study discusses the case of the municipality of Arroio Grande/RS, inserted in this problem by not yet present sanitation planning advocated the legislation. To this end, in addition to the critical literature review and desk research, the study uses interviews and field research. The case study describes the current situation of basic sanitation services and presents suggestions for improvements, showing that, for a quality sanitation infrastructure works only are not enough.